Pendidikan Islam Dalam Spektrum Politik Pendidikan Nasional - Mastur (Fikroh: (Jurnal Studi Islam), 2023)
Discourse on Islamic education will never be separated from the political and cultural dynamics of a society. In the Indonesian context, the dynamics of Islamic education cannot be separated even shackled by the country's political policies and community pluralism which is a reality in Indonesia, both before independence until post-independence Indonesia. Since the first half of the 19th century, the history of Islamic education in Indonesia has begun a new phase marked by shifts and changes in almost all aspects including institutions, methods, curriculum and Islamic education orientation. At that time Islamic education was dominated by traditional educational institutions, namely boarding schools. Indonesia, although it is expressly stated that it is not a religious State and not a secular State, but the Pancasila State. The State of Pancasila, it can be said that Indonesia took the middle path between the religious State and the secular State. The first formulation of the precepts of Pancasila and Article 29 of the 1945 Constitution Paragraph (1) gives a characteristic that is unique to the State of Indonesia, not a secular State that separates religion and State, and not a religious State based on a particular religion. The Pancasila State guarantees the freedom of every citizen to be religious and must maintain noble character based on the values ​​of Pancasila. This is what causes the Indonesian Government to continue to see that religion occupies an important position in this country as a source of prevailing values.